ANALISIS DETERMINAN PENGGUNA PELAYANAN PENCEGAHAN PENULARAN HIV DARI IBU KE ANAK DI PUSKESMAS JATILUHUR TAHUN 2022 - Zebua, Eleonara Solomasi (2022)
Globally, Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) are significant problems in managing the Sustainable Development Goals (SDGs). The problem of HIV is related to the third indicator of the SDGs because it affects the quality of human resources. This can be seen from the increasing incidence of HIV and AIDS and the number of cases that are more than reported. This study was conducted to seek the determinants of PPIA HIV service users at the Jatiluhur Community Health Center, Bekasi City, West Java, Indonesia. This study used a cross-sectional design and the sampling technique was total sampling with a total sample of 171 respondents. The results showed that the variables of health services, family support, mother's knowledge, and HIV stigma were the most influential factors and HIV stigma (POR: 4.673; 95% CI: 1.129-5.055) was the dominant factor. It is recommended that pregnant and lactating women to seek information related to HIV and AIDS, especially regarding HIV transmission and stigma in the community. Community Health Center also need to improve MCH services.